Reliability and accuracy of ball speed during different strokes in young tennis players - González-González, I.; Rodriguez-Rosell, D.; Clavero-Martin, D.; Mora-Custodio, R.; Pareja-Blanco, F.; Yanez-Garcia, J. M.; González-Badillo, J. J. (Sports Medicine International Open, 2018)
This study aimed to examine the relationship between anthropometric and sport level (SL) variables and both ball speed and accuracy in young male competitive tennis players. A secondary aim of this study was to analyze the possible differences in ball speed and accuracy between players of different competitive levels. A total of 85 players (age: 14.7±2.4 years; height: 1.65±0.12 m; body weight: 56.3±13.4 kg) were divided into five groups according to their positions in the ranking list. To measure stroke performances, the goal was to hit 20 balls at the maximum possible speed inside the court, with the opportunity of hitting a maximum of 30 balls for each groundstroke and 40 for serve. Accuracy was calculated by dividing the number of balls inside the default surface by the total number of hits. The ball speed showed high reliability for all three strokes assessed. The ball speed progressively increased as SL increased for all strokes, whereas accuracy remained unchanged across SL groups. All independent variables presented significant relationships (r=0.59-0.85, p<0.05-0.001) with ball speed for all strokes. However, after applying partial correlations these relationships decreased substantially (r=0.02-0.51). The accuracy showed significant relationships with SL only in the serve (r=0.31, p<0.05) and backhand (r=0.26, p<0.05) strokes. In conclusion, the results of the present study suggest that tennis performance depends on increasing ball speed while maintaining a relatively stable level of accuracy.